Synaesthesia and the ancient senses - Butler, Shane, 1970-; Purves, Alex C., 1972-; Cambridge eBooks (Durham : Acumen Publishing, 2013)
Like us, the ancient Greeks and Romans came to know and understand the world through their senses. Yet sensory experience has rarely been considered in the study of antiquity and, when the senses are examined, sight is regularly privileged. Synaesthesia and the Ancient Senses presents a radical reappraisal of antiquity's textures, flavours, aromas, sounds and sights. It offers both a fresh look at society in the ancient world and an opportunity to deepen the reading of classical literature. This book will appeal to readers interested n classical society and literature, philosophy, and social and cultural history. All Greek and Latin is translated, and technical matters are explained for the non-specialist. The introduction sets the ancient senses within the history of aesthetics and the subsequent essays explore the senses throughout the classical period and on to the modern reception of classical literature.
Why are there nine muses? / James I. Porter -- Haptic Herodotus / Alex Purves -- The understanding ear : synaesthesia, paraesthesia and talking animals / Mark Payne -- Aristophanes, Cratinus and the smell of comedy / Mario Telò -- "Looking mustard" : Greek popular epistemology and the meaning of Drimys / Ashley Clements -- Plato, beauty and "philosophical synaesthesia" / Ralph M. Rosen -- Manilius' cosmos of the senses / Katharina Volk -- Reading death and the senses in Lucan and Lucretius / Brian Walters -- Colour as synaesthetic experience in antiquity / Mark Bradley -- Blinded by the light : oratorical clarity and poetic obscurity in Quintilian / Curtis Dozier -- The sense of a poem : Ovids banquet of sence (1595) / Sean Keilen -- Saussure's Anaphonie : sounds asunder / Joshua T. Katz -- Beyond Narcissus / Shane Butler.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Senses and sensation -- History; Aesthetics, Ancient; Electronic books